Changing practice cultures in statutory child protection: Practitioners' perspectives. Issue 1 (16th May 2018) - Cortis, Natasha; Smyth, Ciara; Wade, Catherine; Katz, Ilan
Abstract: Many child protection systems struggle to implement effective models of frontline practice in the context of high caseloads, increasing costs, and compliance‐focused bureaucratic cultures. This article discusses changes brought about by "Practice First, " a framework for practice introduced to improve the quality and effectiveness of child protection work in New South Wales, Australia. Findings drawn from quantitative and qualitative research with practitioners show that the initiative was effective in changing cultures of practice. It enabled workers to spend more face‐to‐face time with families and build relationships and was perceived to improve the quality of decision‐making. At the same time, the article highlights difficulties in attempting to embed change in practice cultures when broader systemic challenges persist.